1998
DOI: 10.1017/s0033291798006734
|View full text |Cite
|
Sign up to set email alerts
|

Patient treatment insistence and medication craving in long-term low-dosage benzodiazepine prescriptions

Abstract: These results provide evidence for drug-seeking or craving behaviour of patients who receive low-dosage benzodiazepine prescriptions. A major problem in benzodiazepine withdrawal occurs before the withdrawal programme has even begun. These data show that benzodiazepine low-dosage dependence should be considered a real form of dependence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
3

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 26 publications
2
21
0
3
Order By: Relevance
“…24 Two-thirds of their 122 primary care patients receiving long-term benzodiazepines rejected the idea of taking a "drug-holiday" of at least 3 weeks in duration. Those individuals were less educated and were using a higher percentage of long-acting benzodiazepines than patients who accepted their proposal.…”
Section: Discussionmentioning
confidence: 99%
“…24 Two-thirds of their 122 primary care patients receiving long-term benzodiazepines rejected the idea of taking a "drug-holiday" of at least 3 weeks in duration. Those individuals were less educated and were using a higher percentage of long-acting benzodiazepines than patients who accepted their proposal.…”
Section: Discussionmentioning
confidence: 99%
“…Although limited, other data regarding predictors of discontinuation exist [16][17][18]. Higher daily benzodiazepine dosage was found to predict refusal to attempt withdrawal [17].…”
Section: Discussionmentioning
confidence: 99%
“…For example, in a cognitive-behavioral therapy discontinuation trial among older insomniac adults, 505 patients were assessed for eligibility, and 440 were excluded for various reasons (i.e., 161 did not meet exclusion criteria, 114 refused to participate and 165 were excluded for "other" reasons), resulting in only 65 randomized to treatment in what thus became an underpowered study [12]. Other investigators have also reported that many chronic benzodiazepine users refuse to consider withdrawal programs [13][14][15][16][17][18]. Older chronic patients' long-term use of benzodiazepines, coupled with their lack of recognition or minimization of side effects and fears of being left suffering without these medications understandably make taper/discontinuation seem an insurmountable task [9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations